2006
DOI: 10.1016/j.jcrs.2006.04.020
|View full text |Cite
|
Sign up to set email alerts
|

Effect of anterior capsule polishing on the posterior capsule opacification–inhibiting properties of a sharp-edged, 3-piece, silicone intraocular lens

Abstract: Three years after cataract surgery, eyes in which the anterior capsule had been polished had significantly less ACO. However, polishing did not lower PCO intensity when a sharp-edged CeeOn 911A IOL was implanted in the bag. Although results indicate that anterior capsule polishing may enhance the development of regeneratory PCO, this trend did not reach statistical significance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
34
0
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 25 publications
2
34
0
2
Order By: Relevance
“…Menapace and collegues 3 have found that ACO rates are significantly lower in polished eyes compared with unpolished eyes at all follow-up examinations. Sacu et al 2 found that although careful anterior capsule polishing reduces ACO and fibrotic PCO, neither can be completely prevented.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Menapace and collegues 3 have found that ACO rates are significantly lower in polished eyes compared with unpolished eyes at all follow-up examinations. Sacu et al 2 found that although careful anterior capsule polishing reduces ACO and fibrotic PCO, neither can be completely prevented.…”
Section: Discussionmentioning
confidence: 92%
“…1 Despite recent progress in cataract extraction techniques, lens implantation techniques, and IOL design, capsular opacification still remains a problem. [2][3][4] Capsular opacification takes place due to proliferation, migration, and differentiation of residual lens epithelial cells (LECs). 5 These LECs attempt to undergo normal differentiation or epithelial mesenchymal transition (EMT), and consequently form heterogeneous groups of cells in the anterior capsule opacification (ACO) and posterior capsule opacification (PCO).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study by Nishi and Nishi found that mechanical intraoperative anterior capsule polishing (ACP) reduces the rate by 7.1% [10]. However, other studies challenge those findings and conclude that changes in surgical technique, such as capsule polishing, fail to prevent PCO [11] [12] [13] [14] [15], although a capsulorhexis size that lies on the optic diameter appears to be beneficial [16]. Moreover, capsular polishing is reported to exacerbate PCO, as found in the long-term follow-up studies [11] [12] [13].…”
Section: Introductionmentioning
confidence: 99%
“…However, other studies challenge those findings and conclude that changes in surgical technique, such as capsule polishing, fail to prevent PCO [11] [12] [13] [14] [15], although a capsulorhexis size that lies on the optic diameter appears to be beneficial [16]. Moreover, capsular polishing is reported to exacerbate PCO, as found in the long-term follow-up studies [11] [12] [13]. In recent years, with the development and rising popularity of new generation of premium (IOLs) like the multifocal, toric, accommodative, the clinical significance of the LEC removal may become more important when a maximum optical zone is required (e.g., multifocal IOLS) [5].…”
Section: Introductionmentioning
confidence: 99%